DIFFERENCES IN INSTALLATION TECHNIQUESTOURNIQUET ON SERUM POTASSIUM RATETHE DIFFERENCES APPLICATION TECHNIQUE OF TOURNIQUETTO POTASSIUM LEVEL IN SERUM - Bastian (Medical Studies and Health Journal (SEHAT), 2024)
Potassium is an important analyte because if there is a deficiency or too much of potassium, it will lead to the death of a person, that is the reason why errors in potassium measurements can create serious conditions for patients if therapy is based on inaccurate laboratory results. The hemoconcentration state of the sample can influence the final results obtained. This research aims to determine application techniquesTourniquet against potassium levels, where useTourniquet Inaccuracy can also cause hemoconcentration of the sample which can increase potassium levels in the serum. This research is a laboratory experiment that uses serum from subjects. All data was then processed statistically with paired T-Test. The results of the research are the average potassium levels using the techniqueTourniquet released right after the vein became accessible was approximately 3.86 mmol/L, lower than the second intervention using applicationTourniquet which is not released until the blood volume is sufficient, around 4.05 mmol/L. According to the results of the paired T Test, the p value is 0.003 with 2 tailed significance (α = 0.025) which makes p < α. These results indicate that there is a difference in potassium levels between the two tourniquet application techniques